Common Risk Factors and the Macroeconomy: New Evidence from the Japanese Stock Market - Lucas Bretschger; Filippo Lechthaler (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
Using new data on returns and risk factors the paper considers the stock performance on the Japanese market, which is the second largest in the world and operates under unique macroeconomic conditions. We find that the CAPM model is not an adequate approach for the Japanese market. The Carhart model performs reasonably well but fails to reject the null hypothesis of a zero intercept for the full period. Extended tests reveal a structural change in asset prices in the year 1998. When separating the sample into two periods, the standard four factor model explains market returns much better. We show that the relation between stock returns and risk factors is affected by macroeconomic conditions, especially when considering the momentum strategy. The Japanese case illustrates the necessity of considering structural instability related to the macroeconomic development, which is especially important for countries and time periods with a sluggish economy.
Keywords: G12; G15; G01; C89; 330; Risk factors; value; size; momentum; Japanese stocks; macroeconomic conditions; structural break; Börsenkurs; Volatilität; Wirtschaftslage; CAPM; Faktorenanalyse; Strukturbruch; Schätzung; Japan